Analysis of Crack Propagation in Composite Materials Using Mixed Finite Elements - Bougueroua Ahmed; Bouzerd Hamoudi (Selected Scientific Papers: Journal of Civil Engineering)
This study investigates the application of fracture mechanics to analyze cracked structures, particularly focusing on cracks along interfaces in multilayer materials. Assuming perfectly plastic elastic behavior, small displacements, and plane structures, the research employs a new mixed finite element, RMQ-7, derived from Reissner’s variational principle. The RMQ-7 element, designed to model both the free edge effect along the crack and continuity in the rest of the material, is used in conjunction with the virtual crack extension method to evaluate the energy release rate and the size of the plastic zone around the crack tip.